The stowaway - Murray, James S. (James Stephen), 1976-; Wearmouth, Darren (St. Martin's Press, 2021)
"From internationally bestselling authors James Murray and Darren Wearmouth comes The Stowaway, a suspenseful masterpiece that leaves a cruise ship stranded at sea with a serial killer hiding aboard... Two years ago, Maria Fontana was the deciding vote on a jury that set alleged serial killer Wyatt Butler free. Now, she and her family are enjoying vacation on a two week long transatlantic cruise. But when passengers are discovered brutally murdered in a similar way to Butler's ritualistic MO, the ship goes on lockdown. Maria, one of only twelve people in the world with intimate knowledge of the case, faces a perilous ticking clock. Is it a copycat? Or is she trapped on board with the bloodthirsty maniac she chose to set free?"--